A Comparative Study in Teaching Practice Supervision In Two Public Universities in Malaysia - Yah Awg Nik; Ahmad Zainuri Loap Ahmad; Arifuddin Abdullah; Hasif Rafidee Hasbollah (2011)
This comparative study attempts to investigate the teaching practice supervision to obtain information on how it is carried out in two prominent universities in Malaysia, University of Malaya (UM) Kuala Lumpur and Sultan Idris University of Education (UPSI) Tanjung Malim, Perak. This is important especially for (UPSI) supervisors as it is professionally beneficial to them. Moreover, some will probably be against the idea of treating trainee teachers as ‘equals’ as they may be very conservative and traditional in their outlook. Based on the study, a new instrument will be proposed to encourage supervisors and trainee teachers to collaborate. Firstly, trainee teachers doing Bachelor of Education (TESL) are required to do teaching practice during their final semester. Secondly, during this teaching practice, each trainee teacher will be assigned a supervising lecturer from the university. Finally, the supervisor’s role is very crucial in helping and guiding, managing and coordinating the trainee teachers’ learning during teaching practice. However, the process of classroom observation practice in (UPSI) has some shortcomings. Therefore, the implementation of the new instrument that is proposed lays a very good firm foundation for both trainee teachers and supervisors to understand the principles of collaboration and cooperation in teacher training and development. We strongly believe that the key principle is our sincere and genuine intention in helping trainee teachers to develop and achieve progress in a truly developmental way.